PERAN ROA, CURRENT RATIO DAN DER DALAM MEMENGARUHI PERTUMBUHAN LABA TERHADAP HARGA SAHAM PADA BANK UMUM YANG TERDAFTAR DI BEI PERIODE 2020-2023 - Sholehah, Rofiqotus; Soeliha, Siti; Widaninggar, Nanda (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Banks play a crucial role in driving national economic growth. Through their obligations, commercial banks collect funds and act as intermediaries for third parties in facilitating the demand and supply of credit, influencing the stability and progress of a country's economy. The objective of this research is to determine the influence of ROA (Return on Assets), current ratio, and DER (Debt to Equity Ratio) on stock prices through profit growth as an intervening variable in commercial banks listed on the IDX for the 2020-2023 period. The population in this study comprises commercial banks listed on the IDX during the 2020 2023 period. The sampling technique was determined using purposive sampling. Data analysis and hypothesis testing in this research utilized the Smart PLS 3.0 application. The results of the direct influence hypothesis testing indicate that ROA, Current Ratio, and DER have a positive but not significant effect on profit growth. ROA and DER have a negative but not significant effect on stock prices, while the current ratio has a significant negative effect. Profit growth has a positive but not significant effect on stock prices, and ROA, current ratio, and DER have a positive but not significant effect on stock prices. Keywords: ROA, Current ratio, DER, profit growth, stock price